2020
DOI: 10.1111/sms.13901
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in cardiac stroke volume during rowing

Abstract: Preload to the heart may be limited during rowing because both blood pressure and central venous pressure increase when force is applied to the oar. Considering that only the recovery phase of the rowing stroke allows for unhindered venous return, rowing may induce large fluctuations in stroke volume (SV). Thus, the purpose of this study was to evaluate SV continuously during the rowing stroke. Eight nationally competitive oarsmen (mean ± standard deviation: age 21 ± 2 years, height 190 ± 9 cm, and weight 90 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…The results confirmed that variation in SV is similar at rest and during exercise (Sejersen et al 2021). The new finding is that at the onset of cycling exercise (i.e., within 5 s) an approximately 2.5-fold increase in SVV developed, related to variation in the ventilatory but not in the hemodynamic variables.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The results confirmed that variation in SV is similar at rest and during exercise (Sejersen et al 2021). The new finding is that at the onset of cycling exercise (i.e., within 5 s) an approximately 2.5-fold increase in SVV developed, related to variation in the ventilatory but not in the hemodynamic variables.…”
Section: Discussionsupporting
confidence: 78%
“…3). This variation in SV does not manifest at rest or when exercise is ongoing and ventilation likely becomes entrained to movement of the legs as demonstrated during rowing (Sejersen et al 2021;Steinacker et al 1993). In summary, variation in SV at the onset of exercise is influenced by the breathing pattern dominated by Rf may to stabilize the trunk and at the same time maintains blood pressure despite a rapid decrease in TPR.…”
Section: Considerationsmentioning
confidence: 93%
See 3 more Smart Citations